One‐Pot Synthesized Nickel‐Doped Hierarchically Porous Beta Zeolite for Enhanced Methanol Electrocatalytic Oxidation Activity. Issue 24 (28th October 2020) - Wei, Xinfa; Li, Yan; Hua, Zile; Chen, Lisong; Shi, Jianlin
Abstract: Hierarchically porous zeolites have been widely explored for catalytic applications owing to their high specific surface area, large pore volume, favorable mass transfer capability and abundant acidic sites. Herein we report the facile synthesis of Ni‐doped hierarchically Beta zeolite (Ni−H‐beta) via one‐pot hydrothermal method, in which Ni is uniformly doped into the zeolite crystalline skeleton in the form of Ni 3+ without any nickel oxides being found. The prepared Ni−H‐beta zeolite shows high performance towards the electrocatalytic methanol oxidation reaction (MOR) with a high current density of 1450 A g −1 at 1.65 V vs RHE, which is higher than most non‐precious MOR electrocatalysts. More importantly, the electrochemical MOR performance has been identified to be closely related to the acidic property of the prepared samples. The increase in Al concentration resulted in the formation of strong acid sites, and the consequent MOR activity enhancement. These results provide valuable knowledge and favor the application of transition metals doped hierarchical zeolite for electrocatalytic MOR. Abstract : Beta is the best : Nickel‐doped hierarchically porous Beta zeolite can be synthesized via a one‐pot method using tetraethylammonium hydroxide and cetyl ammonium bromide as microporous and mesoporous templating agents, respectively. It shown an better performance of electrocatalytic methanol oxidation reaction with the increasing strong acid sites. And it was testified that the strong acid sites is related to Al content.